Delivering on the promise: poly ADP ribose polymerase inhibition as targeted anticancer therapy. Issue 6 (November 2015) - O'Sullivan Coyne, Geraldine; Chen, Alice; Kummar, Shivaani
Abstract : Purpose of review: The article presents the rationale, clinical development, and current status of poly (ADP ribose) polymerase inhibitors (PARPis) as anticancer agents. Recent findings: The recent approval of olaparib in heavily pretreated patients with advanced ovarian cancer carrying a BRCA1/2 mutation represents a significant therapeutic advance for patients with this difficult to treat disease. Though olaparib is the first agent in this class to be approved, multiple PARPis are in various stages of clinical development, including in combination with other treatment modalities such as radiation, antiangiogenic agents, and cytotoxic chemotherapies. Summary: Clinical benefit has been observed with PARPis in patients with advanced BRCA1/2 mutant ovarian and breast cancers. Various PARPis, either as single agents or in combination, are being evaluated in the neoadjuvant, adjuvant, and metastatic settings.